PTHrP-induced hypercalcemic psychosyndrome under combined anti-PD-L1 and anti-EGFR inhibition in penile squamous cell carcinoma – A case report - Lea Jessica Albrecht; Viktor Grünwald; Jürgen C. Becker; Ralf Gutzmer; Livia Asan; Ellen Uslar; Alexandra Eilers; Anne-Christine Müseler; Alexander Roesch; Dirk Schadendorf; Lisa Zimmer; Elisabeth Livingstone (EJC Skin Cancer)
Introduction: Paraneoplastic hypercalcemia is a life-threatening complication and is usually caused by tumoral secretion of parathyroid hormone-related peptide (PTHrP). Endocrinopathies are common adverse events of immune checkpoint inhibitor (ICI) therapy, but only few reports describe ICI-induced hypercalcemia. Case description: We report the case of a 56-year-old patient with penile cutaneous squamous cell carcinoma (cuSCC) who experienced progression after adjuvant radiochemotherapy. Within the AliCe trial, a multicenter, single-arm phase-II study for stage III/IV non-resectable/metastatic cuSCC, he received avelumab (anti-programmed cell death-ligand 1 antibody) in combination with cetuximab (anti-epidermal growth factor receptor antibody). Two hours after the initial treatment, the patient developed severe delirium, initially unresponsive to symptomatic treatment. Paraneoplastic hypercalcemia was diagnosed on the basis of decreased parathyroid hormone, normal calcitriol, and elevated PTHrP levels. Although ICI-related hypercalcemia could not be fully ruled out, study treatment was continued without further neurological symptoms, but had to be discontinued due to disease progression. The patient showed a good response to palliative chemotherapy lasting 10 months before he died due to progressive disease. Conclusion: This case demonstrates the potential risk of severe hypercalcemia. While hypercalcemia of malignancy is associated with an unfavorable prognosis, immune-mediated hypercalcemia should be considered in patients receiving ICI.